Propuesta de un plan de comunicación estratégica y relaciones públicas para crear una imagen competitiva del Centro Quirúrgico "Da Vinci" de reciente formación, ubicado al norte de la ciudad de Quito - García Correa, Belén Andrea (2012)
The ambulatory surgery centers are medical facilities that provide surgical care of low and medium complexity procedures such as laser green, plastic surgery, among others, in order to reduce hospitalization time and also the cost during their stay. Centro Quirúrgico Da Vinci created to perform outpatient surgical procedures, with a maximum recovery stay of eight hours. Manages an open schema care, where any surgeon who requires outpatient services can make use of infrastructure. However, it has specialized because of the investment partner and the medical center in the area of Urology, offering the full range of medical services in this branch of health. Public relations now play an important role in organizations to interact and manage relationships between the organization and the public. The main objective is to strengthen the image by right communication tools to be used in accordance with the objectives of the organizations. In this context, the graduation work seeks to link the degree of public relations exercise to strengthen the image of Centro Quirúrgico Da Vinci which conducted a field investigation, which allowed the diagnosis of the current image, concluding that the level of knowledge by physicians is low. Furthermore this research is based on a theoretical framework that allowed reviewing the different positions of Public Relations and Communications, as a result is a proposal that would strengthen relations between the Centro Quirúrgico Da Vinci and its related public.